ICT-enabled self-determination, disability and young people. Issue 8 (3rd July 2019) - Pacheco, Edgar; Lips, Miriam; Yoong, Pak
ABSTRACT: Research and practice about self-determination in the context of disability has centred on teaching skills and providing support to help people with impairments to be independent. However, limited research exists about the impact of Information and Communication Technologies, in particular social media and mobile devices, on the development of self-determination skills among people with disabilities. This paper presents the findings of a qualitative study which collected data from observations, a researcher diary, focus groups, individual interviews and data from social media. The focus of the study was on young people with vision impairments who were transitioning to university life. The study found that the participants developed self-determination skills by using and adapting collaborative and interactive online tools and mobile devices according to their transition needs. This finding expands the understanding of the implications of new technologies for young people with disabilities' personal development and the enhancement of self-determination.